Ecological scales and use rights: the use of multiagent systems - Bousquet, Francois; Le Page, C.; Antona, M.; Guizol, P. (2000)
The interactions between natural forest dynamics have to be taken into account when managing the use of forest resources. Simulation models were developed to improve the understanding of this complex system of interactions. Models of multi agent systems are effective tools for studying the dynamics of complex adaptive systems. Several simulation models were developed to study the use of forest resources. This paper presents a model designed to understand the interaction between fuel wood consumption and landscape dynamics. The hypothesis put forward suggests that fuel wood consumption can explain the landscape changes that occur in the Kayanza region of Burundi. The second hypothesis is that a sustainable use of resource must keep steady the fuel wood consumption level per capita over time. A preliminary map was outlined.